Jesús Ponce Cárdenas (2023). Escolios gongorinos. Biografía, anotaciones y defensas - Fadón Duarte, Alberto (Edad de Oro, 2024)
Jesús Ponce Cárdenas (2023). Escolios gongorinos. Biografía, anotaciones y defensas. Madrid/Frankfurt am Main: Iberoamericana/Vervuert, 284 pp. [ISBN 978-84-9192-374-9].